Generation and obduction of ophiolites: Constraints from the Bay of Islands Complex, western Newfoundland - Cawood, Peter Anthony; Suhr, G (Tectonics, 1992)
Constraints provided by the Bay of Islands ophiolite complex (BOIC), western Newfoundland, suggest that its generation, as well as its obduction, is related to collision of the Dunnage Zone island arc system with the irregular continental margin of eastern North America. The constraints include the supra-subduction zone setting of the BOIC; its extensional environment of generation; the synchronous occurrence of ophiolite generation with initiation of drowning and deformation of the North American continental margin; and the restriction of the BOIC, as well as other Appalachian ophiolites and associated Taconian allochthons, to reentrants in thc North American margin. During the early phases of collision of the Dunnage arc with the North American margin, subduction of old oceanic lithosphere trapped in reentrants will continue and allow the development of two potential sites of ophiolite generation. The first develops through trench rollback, leading to ophiolite generation in the overriding arc plate outboard of the reentrant, whereas the second develops in a transtensional environment with spreading centers offset by strike-slip faults which propagate through the overriding plate away from the indenter promontory. The configuration of the BOIC spreading ridge normal to the continental margin, and the direction of initial obduction parallel to the margin, favor generation of the ophiolite in an overall strike-slip regime. With complete subduction of the oceanic remnant, extension in the overriding plate ceases, and the buoyant newly formed oceanic lithosphere is obducted onto the continental margin. Diachronous collision of the arc with the irregular continental margin accounts for the range of ages for ophiolite generation and obduction observed within the Dunnage Zone, and for termination of arc volcanism along the North American margin.